Mission Valley Viaduct Piledriving - 1998 DFI Conference Seattle, Washington October 8, 1998 - David A. Jack (Deep Foundations Institute, 1998)
The Mission Valley Viaduct is located in San Diego, California. This structure is the intersection of Interstate 8 and 805. The project consists of the main viaduct, 8 connecting ramps, and one highway overpass. This job was originally built back in the 70's. After the Loma Prieta Earthquake in 1989, Caltrans began an aggressive program to seismic retrofit all of its bridges throughout the state. Most retrofit designs required major upgrades to the existing footings. These footing upgrades consisted of either driven or drilled shaft piling. The existing footings of the Mission Valley interchange were supported on driven H pile. The soils throughout the site were dense sands and gravels, cobbles, occasional boulders with a dense sandstone bearing strata, which varied through out the site. It was this sandstone strata that the engineers designed their pile tips around. High ground water in sandy soils created a high probability of liquefaction in all of the upper stratas.